A new method with integration of matching and decoupling for MIMO antenna applications. Issue 12 (27th October 2022) - Li, Shun; Chu, Qing‐Xin
Abstract: A novel design concept of multiple‐input and multiple‐output (MIMO) antenna with aiming to improve matching and port isolation at the same time is proposed. As the only additional component, a cross resonator is connected between the two patch antennas. The equivalent circuit model and calculation formula of resonant frequency of cross resonator in differential mode (DM) and common mode (CM) state are given, respectively. The same resonant frequency in the two states is the goal to want, and which is proved to be achievable by the relevant expression. Then, the two port antenna system can obtain good matching and high isolation. The coincidence between simulation and measured results brings the possibility of practical implementation.